Formação colegiada em química: mentoria e autoformação metacognitiva - Rodrigues, Luciana do Nascimento (2023)
The present research adopts a combined approach that integrates quantitative and qualitative methods in its analysis. It falls within the scope of concurrent design intervention research and presents the results of a doctoral study with the aim of understanding how professionals in initial and ongoing education face the challenges arising from changes in Brazilian education. The primary objective of the research is to identify strategies to address these educational and social challenges, empowering teachers to play a proactive role in their own development amid the constant changes in the educational context. Additionally, the research explores how metacognitive strategies proposed by Joseph Flavell can contribute to the ongoing education of high school teachers in the natural sciences, with an emphasis on the subject of chemistry. The theoretical framework adopted encompasses the theories of Maurice Tardif, who provides a critical analysis of teacher education, emphasizing the importance of experiential knowledge as an outcome of an individual construction process that gains significance when shared and validated through professional socialization processes. Another relevant author is Antônio Nóvoa, who promotes collegiality as a theoretical and methodological strategy that values collaboration among teachers and teamwork as a means to develop new educational knowledge. Based on the contributions of Tardif and Nóvoa, the research proposes a mentorship and collegial formation approach, along with Flavell's metacognitive strategies, as an appropriate perspective to deal with constant changes in the field of education. Flavell highlights the importance of metacognition as a significant tool in the learning process. Furthermore, the concept of meaningful learning, as proposed by David Paul Ausubel, is also considered, emphasizing the direct relationship between knowledge accumulation and more efficient learning. The materials used in the research were validated through a pilot test during the supervised internship courses I and II of the full degree program in chemistry at the Federal University of Espírito Santo (UFES). The collected data were analyzed, reviewed, and adjusted. The research was implemented through the participation of teachers in a continuing education course conducted in a remote format during the pandemic period caused by Sars-Cov-2. In this scenario, the research author acted as a facilitator of working groups composed of teachers from diferente Brazilian networks and states, conducting training through synchronous meetings. These groups were supported by mentors, who were master's and doctoral students from the Laboratory of Chemistry Teaching Research (LAPEQ) at the university. Based on these theoretical references, the research and project participants focused on the methods of "metacognitive self-training," "mentored training," and "group training" in the context of chemistry teacher education in the natural sciences. The number of highly educated teachers interested in undergoing training highlights the lack of initial and ongoing education, as well as the lack of preparedness on the part of teachers to begin the 2022 school year planning for the New High School. The results obtained and the triangulation of ideas, which involve the subjects (I, you, we) and the theoretical-methodological framework, revealed that professional development plays a crucial role in promoting more comprehensive, effective, and enriching learning. The interaction between individual, peer, and group methods allowed participants to benefit from various perspectives, experiences, and knowledge, thereby strengthening the learning and training process.